2009
DOI: 10.1111/j.1460-2466.2008.01407.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported News Attention Does Assess Differential Processing of Media Content: An Experiment on Risk Perceptions Utilizing a Random Sample of U.S. Local Crime and Accident News

Abstract: Evidence for media effects in survey research often depends upon measures of selfreported attention to various types of media content, under the assumption that such attention measures gauge the extent of cognitive processing of content. However, effects associated with self-reports of attention might often be due to reverse causation (the attitude or knowledge tested as the outcome might in fact give rise to self-reports of greater attention) or third variable effects. To better assess whether self-reported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…After dropping one low-loading item the inventory was scored for a 7-item composite which had α = .77. Similar items have been used to assess aspects of reactions to advertising with younger samples and are variously termed affective response, liking, or attention (M. Chen, Grube, Bersamin, Waiters, & Keefe, 2005; Slater, Goodall, & Hayes, 2009; Unger, Schuster, Zogg, & Stacy, 2003); we use the latter term.…”
Section: Methods and Samplementioning
confidence: 99%
“…After dropping one low-loading item the inventory was scored for a 7-item composite which had α = .77. Similar items have been used to assess aspects of reactions to advertising with younger samples and are variously termed affective response, liking, or attention (M. Chen, Grube, Bersamin, Waiters, & Keefe, 2005; Slater, Goodall, & Hayes, 2009; Unger, Schuster, Zogg, & Stacy, 2003); we use the latter term.…”
Section: Methods and Samplementioning
confidence: 99%
“…Thus, people's attention to media messages can affect persuasive and learning effects. Consequently, media attention has been regarded as an important predictor of message influence (Slater et al, 2009). Recent studies have shown positive relationships between media use and PEBs.…”
Section: Media Attentionmentioning
confidence: 98%
“…Media attention refers to people's tendency to consciously devote cognitive effort to particular types of media messages (Slater, Goodall, & Hayes, 2009). Several models of information processing and persuasion, such as the elaboration likelihood model (Petty & Cacioppo, 1986), propose that attention to message content is a necessary condition for persuasive effects.…”
Section: Media Attentionmentioning
confidence: 99%
“…Neuwirth, Dunwoody, and Griffin (2000) used protection motivation theory to investigate the role of threat and efficacy in news coverage of risks on willingness to take protective action. Although not intentionally persuasive, news may incidentally influence health-relevant variables, including risk perceptions and concern (see Slater, Goodall, & Hayes, 2009;Slater, Hayes, & Ford, 2007), policy support (Yanovitzky, 2002;Yanovitzky & Bennett, 1999), and behavior (see Pierce & Gilpin, 2001).…”
Section: H1n1 Virusmentioning
confidence: 99%